Rancang Bangun Aplikasi Smart Trolley Dengan Teknologi Barcode Pada Supermarket - Christavian, Yosua; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
In the peak season and at the - time promo supermarkets give a compelling that the number of a dense customer shop in supermarkets. This means so long queues and the customer have to wait a queue to pay for. Customer only buy one thing would have to wait the long queues. The impact of the long queues make customer impatient in the queue , so that happening accruing the customer break to shop in supermarkets. The application of smart trolley with technology barcode a supermarket can help customer in the process of transactions queue independently and process fast payment without waiting for forever a long queue. And for payment or annulment not so buy the process happened in cash. With the application smart trolley it can provide solutions for supermarkets to overcome forever a long queue at the checkout payment. Based on the results and a pilot system, have shown that application smart trolley with technology barcode a supermarket can speed time service therefore time wait a queue become more short.